Phenotypically and genotypically estimation of virulence factors in Salmonella serovar typhi isolated from patients with enteric fever in Al- Najaf, Iraq - LIQAA SALIM; ZAHRAA YOSIF MOTAWEQ (Smujo International, 2022)
Abstract. Zghair LS, Motaweq ZY, Lafta HC. 2022. Phenotypically and genotypically estimation of virulence factors in Salmonella serovar typhi isolated from patients with enteric fever in Al-Najaf, Iraq. Nusantara Bioscience 14: 128-133. Salmonella serovar typhi, often known as enteric fever, causes typhoid fever and has been a major human infectious disease for centuries, surviving in poor sanitation and overcrowding. Only 64 (58.1%) Gram-negative bacteria were found from the 110 total specimens, with 46 (41.8%) Gram-positive bacteria. The 64 samples were divided into 42 (65.6%) males and 22 (34.4%) females. This work presents the isolation and identification of 64 Salmonella typhi isolates obtained from specimens. In addition, the flagellin gene was found in 64 isolates of probable typhoid fever patients (fliC-d). In this study, phenotypic techniques were used to detect several virulence factors. The results showed that small colonies of L-form bacteria grow on the edges of a petri dish when one of the ?-lactam antibiotics (a class of antibiotics that includes penicillin) is given to wild-type bacteria, showing 52 (81.3%) of isolates could produce L-form and observed in 44 (68.75%). The ability to generate CFA/I and CFA/II was found in 68.7% of isolates. The large percentage of CFA produced showed CFA/III production, 64 (100%).